Genetic diversity of lowland and montane populations of Polygonatum verticillatum (L.) All. Determined on the basis of isozymatic analysis - Szczecińska, Monika; Hołdyński, Czesław; Sawicki, Jakub (Biodiversity: Research and Conservation, 2006)
This study aimed to determine the genetic diversity of Polygonatum verticillatum (L.) All., and to estimate the degree of genetic similarity between 18 Polish populations of this species: 9 from the lowlands in the north and 9 from the mountains in the south of Poland. Five enzymatic systems (AAT, EST, GDH, LAP and MDH) revealed 13 loci. Polymorphism was observed at the Aat3 locus and all esterase loci. An isozymatic analysis did not show any significant differentiation between lowland and montane populations, and genetic similarity between the two groups was high (I = 0.95). The results suggest that in the past this species had a continuous geographic range in Poland or that the populations examined originated from the same geographic refuge.